Perceptions and reasons of E-cigarette use among medical students: an internet-based survey - Abdulmohsen A. Alzalabani; Sheref M. Eltaher (SpringerOpen, 2020)
Abstract Background Nowadays, E-cigarette use shows a significant increase among adults and youth in many countries, although there is still a public health debate about its relative effects compared to the traditional cigarettes. Objectives To assess the prevalence, perceptions, possible reasons of use, and factors associated with E-cigarettes use among medical students at Taibah University, Kingdom of Saudi Arabia. Methods An internet-based online survey study was conducted between September and November 2019 which contains socio-demographic data, data related to smoking and E-cigarette use, and data related to reasons of E-cigarette use. Results A total of 527 out of 720 students completed an online questionnaire, 15.9% of the surveyed students used E-cigarettes, older age, male, higher college class, those who have ≥ 1 close friend who smokes, family history of smoking, and housemates who smoked E-cigarettes show a significantly higher percentage of E-cigarettes use. The first reason for E-cigarettes use namely that, E-cigarette helps to reduce tobacco consumption with no intention to quit smoking was the highest (89.2%), followed by E-cigarette being less toxic than tobacco (88.4%), and finally E-cigarette helps to avoid having to go outside to smoke (62.05%). Logistic regression analysis showed that sex, more than one close friend who smokes, family history of smoking, and housemates who smoked E-cigarettes were significant factors associate with its use. Conclusion E-cigarette use appears to be relatively common than conventional cigarette among the participants. Our study participants perceived that it can help people quit, less harmful, and less addictive. The most common reason for its use among the study participants was that E-cigarette helps to reduce tobacco consumption in users with no intention to quit smoking.